"Put on the Full Armor of God": Evangelical Spiritual Warfare and Civic Engagements at the Margins of Latin American Cities - Reu, Tobias (International journal of Latin American religions, 2025)
Spiritual warfare has become a principal subject of scholarly work on the intersection of evangelical Christianity and right-wing politics. According to a prevalent narrative, it mainly provides a metaphor for the extension of the demonization of the political other into the realm of divine truths. However, as a theological trope disseminated through evangelical media and international church networks, spiritual warfare also arrives at the margins of Latin American societies, where the hegemonic projects of right-wing politicians and their evangelical allies are but distant references. Here, spiritual warfare motivates engagements with the ills of living in violent and precarious environments. This article draws on ethnographic material obtained between 2013 and 2019 through fieldwork in Guatemala and Bolivia to address the vernacularization of evangelical spiritual warfare and its impact on civic subjectivities at the margins of Latin American cities. The argument pursued is twofold. On the one hand, the goal is to underscore the political dimension of spiritual warfare as a specific theological trope that structures evangelical engagements with space, nation, secular society, and ethnic and spiritual others. On the other hand, attention is drawn to vernacular mobilizations of the theological trope of spiritual warfare, which emerge in its local appropriation and exceed the political intent inherent in its original conceptualizations.